Step-by-step explanation:
![\large\underline{\sf{Solution-}}](https://tex.z-dn.net/?f=%5Clarge%5Cunderline%7B%5Csf%7BSolution-%7D%7D)
Given that,
Sum of the digits of a two digit number is 9
<em>So, Let we assume that </em>
![\begin{gathered}\begin{gathered}\bf\: Let-\begin{cases} &\sf{digit \: at \: tens \: place \: be \: x} \\ \\ &\sf{digits \: at \: ones \: place \: be \: 9 - x} \end{cases}\end{gathered}\end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%5Cbegin%7Bgathered%7D%5Cbf%5C%3A%20Let-%5Cbegin%7Bcases%7D%20%26%5Csf%7Bdigit%20%5C%3A%20at%20%5C%3A%20tens%20%5C%3A%20place%20%5C%3A%20be%20%5C%3A%20x%7D%20%20%5C%5C%20%5C%5C%20%26%5Csf%7Bdigits%20%5C%3A%20at%20%5C%3A%20ones%20%5C%3A%20place%20%5C%3A%20be%20%5C%3A%209%20-%20x%7D%20%5Cend%7Bcases%7D%5Cend%7Bgathered%7D%5Cend%7Bgathered%7D)
Thus,
![\begin{gathered}\begin{gathered}\bf\: So-\begin{cases} &\sf{number \: formed = 10 (9 - x) + x = 90 - 9x} \\ \\ &\sf{reverse \: number = 10x + 9 - x= 9x + 9} \end{cases}\end{gathered}\end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%5Cbegin%7Bgathered%7D%5Cbf%5C%3A%20So-%5Cbegin%7Bcases%7D%20%26%5Csf%7Bnumber%20%5C%3A%20formed%20%3D%2010%20%289%20-%20x%29%20%2B%20x%20%3D%2090%20-%209x%7D%20%5C%5C%20%5C%5C%20%20%26%5Csf%7Breverse%20%5C%3A%20number%20%3D%2010x%20%2B%209%20-%20x%3D%209x%20%2B%209%7D%20%5Cend%7Bcases%7D%5Cend%7Bgathered%7D%5Cend%7Bgathered%7D)
<em>According to statement </em>
When we interchange the digits, it is found that the resulting new number is greater than the original number by 27.
![\rm\implies \:9x + 9 - (90 - 9x) = 27](https://tex.z-dn.net/?f=%5Crm%5Cimplies%20%5C%3A9x%20%2B%209%20-%20%2890%20-%209x%29%20%3D%2027)
![\rm\implies \:9x + 9 - 90 + 9x = 27](https://tex.z-dn.net/?f=%5Crm%5Cimplies%20%5C%3A9x%20%2B%209%20-%2090%20%20%2B%209x%20%3D%2027)
![\rm\implies \:18x - 81 = 27](https://tex.z-dn.net/?f=%5Crm%5Cimplies%20%5C%3A18x%20%20-%2081%20%3D%2027)
![\rm\implies \:18x = 27 + 81](https://tex.z-dn.net/?f=%5Crm%5Cimplies%20%5C%3A18x%20%20%3D%2027%20%2B%2081)
![\rm\implies \:18x = 108](https://tex.z-dn.net/?f=%5Crm%5Cimplies%20%5C%3A18x%20%20%3D%20108)
![\rm\implies \:\boxed{\tt{ x = 6}}](https://tex.z-dn.net/?f=%5Crm%5Cimplies%20%5C%3A%5Cboxed%7B%5Ctt%7B%20x%20%20%3D%206%7D%7D)
So,
![\begin{gathered}\begin{gathered}\bf\:\rm :\longmapsto\:\begin{cases} &\sf{digit \: at \: tens \: place \: be \: 6} \\ \\ &\sf{digits \: at \: ones \: place \: be \: 3} \end{cases}\end{gathered}\end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%5Cbegin%7Bgathered%7D%5Cbf%5C%3A%5Crm%20%3A%5Clongmapsto%5C%3A%5Cbegin%7Bcases%7D%20%26%5Csf%7Bdigit%20%5C%3A%20at%20%5C%3A%20tens%20%5C%3A%20place%20%5C%3A%20be%20%5C%3A%206%7D%20%20%5C%5C%20%5C%5C%20%26%5Csf%7Bdigits%20%5C%3A%20at%20%5C%3A%20ones%20%5C%3A%20place%20%5C%3A%20be%20%5C%3A%203%7D%20%5Cend%7Bcases%7D%5Cend%7Bgathered%7D%5Cend%7Bgathered%7D)
![\begin{gathered}\begin{gathered}\bf\: So-\begin{cases} &\sf{number \: formed = 90 - 9x = 90 - 54 = 36} \\ \\ &\sf{reverse \: number = 9x + 9 = 54 + 9 = 63} \end{cases}\end{gathered}\end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%5Cbegin%7Bgathered%7D%5Cbf%5C%3A%20So-%5Cbegin%7Bcases%7D%20%26%5Csf%7Bnumber%20%5C%3A%20formed%20%3D%2090%20-%209x%20%3D%2090%20-%2054%20%3D%2036%7D%20%5C%5C%20%5C%5C%20%20%26%5Csf%7Breverse%20%5C%3A%20number%20%3D%209x%20%2B%209%20%3D%2054%20%2B%209%20%3D%2063%7D%20%5Cend%7Bcases%7D%5Cend%7Bgathered%7D%5Cend%7Bgathered%7D)
<em><u>Thus, 2 digit number is 36</u></em>
▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬
<h2>Basic Concept Used :- </h2>
Writing System of Linear Equation from Word Problem.
1. <em>Understand the problem. </em>
Understand all the words used in stating the problem.
Understand what you are asked to find.
2. <em>Translate the problem to an equation. </em>
Assign a variable (or variables) to represent the unknown.
Clearly state what the variable represents.
3. <em>Carry out the plan and solve the problem.</em>